UNA NUEVA SECCIÓN EN EBM.RECIDE: SUPLEMENTOS MONOGRÁFICOS - Ernesto De la Cruz Sánchez; Sebastián Feu Molina (Federación Extremeña de Balonmano; University of Extremadura, 2011)
EBM.RECIDE introduces monographic supplements, a new journal section designed to highlight the progress in a specific field. The publication of these studies is intended to show recent advances in a specific knowledge area of sport sciences. This new section's main objective is to propose a set of studies with a common field, addressing the same topic through multiple perspectives and different methodological approaches. This new issues will provide the reader with a whole focus of a determined knowledge area and compare the different ways of research taking place in a field of interest. In this first supplement, we published a selection of the best papers presented at the Ist International Congress of Combat Sports held in Murcia, 9 to December 12, 2010, in the official languages of English and Spanish. Works appearing in this supplement have been carefully selected to meet the criteria of scientific interest and quality outlined above. Keys words: Supplements, Combat Sports.